Entrepreneurial Capital in Rural Environments and Business Performance: Insights from Young Entrepreneurs - Hifzhan Frima Thousani; Mochammad Heri Edy (Universitas Muhammadiyah Palu, 2024)
Rural entrepreneurship is a new concept that has been recognized as a vital component in the development of a country's economy. However, little is known about the role of rural entrepreneurship capital in influencing the actions of young entrepreneurs in rural areas. This study employs a quantitative methodology utilizing purposive sampling technique. A total of 733 questionnaires were collected and deemed valid for this study. The results of hypothesis testing reveal that the relationship between CC (Cultural Capital) and FP (Firm Performance) is the most robust among all variables. Moreover, the findings highlight the importance of education, familial backing, and entrepreneurial networks within rural environments for the success of young individuals. The findings of this study can offer valuable perspectives for future research endeavors and can aid in improving educational initiatives aimed at nurturing entrepreneurship among young people.